USING ANALYTIC HIERARCHY PROCESS TO DEVELOP HIERARCHY STRUCTURAL MODEL OF CONSUMER DECISION MAKING IN DIGITAL MARKET - Depeesh Kumar Singh,; Anil Kumar,; Manoj Kumar Dash, (Asian Academy of Management Journal, 2016)
In today's electronic era, e-commerce market is a very fast growing market. With the proliferation of the internet and web applications, customers are increasingly interfacing and interacting with web-based applications. They are shifting themselves offline to online which is creating challenging environment for the service providers to meet them according to their customise needs. It is, therefore, not only to find out the important but also to prioritise the factors which influence customer to online purchasing. The main purpose of this study is to develop a Hierarchy Structural Model (HSM) of consumer decision making in the digital marketplace. To achieve the objective of the study, criteria and their sub-criteria are determined through an extensive literature review and a structured questionnaire is prepared to data from experts through a personal interview on the scale of 1 to 9. Analytic Hierarchy Process (AHP), a multi-criteria decision making mathematical tool has been applied for analysis of the importance of each criteria and to develop a hierarchy of criteria for importance. As per weight estimated through HSM modal, the criteria "information and e-service quality" is the most important one followed by the criteria "online reputation" and "incentives and post-purchase" in online purchasing. Online service providers should focus on these essential criteria to enhance their e-service quality, satisfaction and retention consumer and their online reputation.